2011
DOI: 10.1007/s11999-010-1475-5
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Abnormalities and Genetic Factors Related to Vertical Talus

Abstract: Background/rationale Congenital vertical talus is a fixed dorsal dislocation of the talonavicular joint and fixed equinus contracture of the hindfoot, causing a rigid deformity recognizable at birth. The etiology and epidemiology of this condition are largely unknown, but some evidence suggests it relates to aberrations of skeletal muscle. Identifying the tissue abnormalities and genetic causes responsible for vertical talus has the potential to lead to improved treatment and preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Mutations in the HOXD10 7 and GDF5 8 genes have been identified in some patients with isolated vertical talus, with many additional genetic factors remaining unknown. Indeed, primary muscle abnormalities have been found on muscle biopsies in some cases 9 . Although both isolated and non-isolated vertical tali pose treatment challenges, it is generally accepted that non-isolated cases are more rigid and less responsive to treatment 10,11 .…”
mentioning
confidence: 99%
“…Mutations in the HOXD10 7 and GDF5 8 genes have been identified in some patients with isolated vertical talus, with many additional genetic factors remaining unknown. Indeed, primary muscle abnormalities have been found on muscle biopsies in some cases 9 . Although both isolated and non-isolated vertical tali pose treatment challenges, it is generally accepted that non-isolated cases are more rigid and less responsive to treatment 10,11 .…”
mentioning
confidence: 99%
“…Primarily, it has been linked to disorders such as distal arthrogryposis and myelomeningocele, and an array of chromosomal abnormalities, single gene defects and known genetic conditions [5] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…If untreated it can cause substantial pain and disability. Its incidence is approximately 1 in 100,000 live births, with no sex predilection, and it has association with neuromuscular abnormalities and identified genetic syndromes in 50% of cases [1-5]. This report presents a case of congenital vertical talus in an infant with Cri du Chat Syndrome (CdCS), which - so far as we are aware - has not been previously reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology and epidemiology of this condition are largely unknown, but some evidence suggests it relates to aberrations of skeletal muscle. Merrill et al 42 identified associated congenital anomalies and genetic abnormalities in sixty-one patients affected with vertical talus. They obtained abductor hallucis muscle biopsy specimens from the affected limbs of eleven of the sixty-one patients and compared the histopathologic characteristics with those of age-matched control subjects.…”
Section: Foot and Anklementioning
confidence: 99%